Individual ostracode valve analyses of Sclerocypris clavularis from modern Lake Turkana sediments - Thirumalai, Kaustubh; Cohen, Andrew N; Taylor, Dustin (PANGAEA, 2023)
We provide stable carbon (δ¹³C) and oxygen (δ¹⁸O) isotope measurements in individual calcitic valves of extant ostracode species, Sclerocypris clavularis, from modern sediments in 17 sites across Lake Turkana, eastern Africa. These sediments were collected using a modified Ekman dredge during May-November, 1979. Pooled statistics of these individual ostracode valve analyses (IOVA) of δ¹³C and δ¹⁸O measurements (n = 329) at each site show strong correlations with lake hydrological parameters. Within-site variance in IOVA-δ¹³C is larger (~60%) than that of IOVA-δ¹⁸O. Yet, pooled averages exhibit a systematic pattern with higher δ values towards the southern part of the lake, away from Omo River inflow, which is the largest riverine input into Lake Turkana (comprising ~90% of overall inflows). We suggest that the latitudinal δ¹³C gradient may arise from low riverine δ¹³C and low organic matter δ¹³C as a productivity response to nutrient-rich Omo River inflow towards the north. The δ¹⁸O pattern may be explained by the diminishing influence of Omo River inflows and more evaporation driving higher IOVA-δ¹⁸O values towards the windier, southern basin. We conclude that pooled IOVA statistics in Omo-Turkana sediments can aid interpretations of past regional paleohydrology and its variability in this basin.
Keywords: lake sediments; ostracodes; oxygen and carbon isotopes